The religious aspects of the Scottish covenanting armies, 1639-1651 - Furgol, EM (1983)
﻿While historians of Britain in the 1640s have long been attracted by the English New Model Army and in recent years by the English royalist armies, the armies fielded by the Scottish Covenanters have suffered a strange neglect. It was not until the work on this thesis was well- advanced that the crude nature of previous efforts became apparent. In an attempt to provide a basic understanding of the Covenanting forces, this thesis synthesizes a mass of material relating to the religious aspects of the armies. Two crucial questions emerged: did the military reflect Scottish society or any part of it; were the Covenanters' forces godly armies seeking to evangelize the areas they occupied? These themes have been interpreted broadly to include the rules of war, the army chaplains, religious manifestations in military life, the moral behaviour of the soldiers, and the role of the armies in spreading the presbyterian faith. In addition to those topics, an examination of the soldiers' relations with civilians and the political activities of the military have been included. The first most clearly allows one to determine whether the Covenanting armies attained the status of godly armies. The political question arises out of the close relationship between religious and political activities in the period. With the exception of family legal papers the entire spectrum of Scottish seventeenth-century sources was inspected. The records of the 1.Estates and its committees, the General Assembly and its Commission, form the basic sources for a view of national developments. At the local level the burgh, presbytery, family and kirk session records proved invaluable. Unfortunately few diaries, memoirs or letters survived. English materials primarily state papers, pamphlets and news books were also helpful. The findings of this thesis suggest that the armies of the Covenanters failed to achieve the ideals set for them.